E0562 Impact of circumferential pulmonary vein isolation on electrophysiologic properties of pulmonary veins in patients with paroxysmal atrial fibrillation. (17th November 2010) - Zheng, Zhitao; Xia, Yunlong; Gao, Lianjun; Zhang, Shulong; Yang, Donghui; Yin, Xiaomeng; Cong, Peixin; Chang, Dong
Abstract : Objective: The special electrophysiological characteristics of pulmonary veins (PVs) are highly correlated with the incidence of Atrial fibrillation (AF), and circumferential PV isolation (CPVI) has been demonstrated to be effective in many patients with paroxysmal AF (PAF). However, the impact of CPVI on electrophysiologic properties of PVs is still rarely known. Methods: Eighteen patients (58.4±9.3 years old, 9 males) with frequent symptomatic and drug-resistant PAF were enrolled in this study. Under CARTO and Ensite Navx's guidance (13 Carto, 5 Ensite Navx), CPVI was performed in these patients, and totally 72 PVs were isolated, which was confirmed by the disappearing of PV potentials recorded by using the 10-pole circular catheter during sinus rhythm, in the first procedure. Effective refractory period (ERP), Relative Refractory Period (RRP) and Functional Refractory Period (FRP) were measured by use of programmed stimulation with a single extrastimulus in the PVs and left atrial (LA) before and after ablation in each patient. Due to can't record PV potential or cant't pace the PVs after CPVI, the changes of electrophysiologic properties of 33 PVs were used for final analysis. Results: No change of pacing threshold of PVs and LA was found before and after CPVI (3.2±0.6 V vs 3.3±0.5 V and 3.3±0.7 V vs 3.2±0.7 V, respectively, p>0.05). Before CPVI, the ERP and RRP of PVs (187±60 msec and 223±45 msec) were significantly shorter than that of the LA (229±31 msec, p<0.001 and 261±34 msec, p<0.05). After CPVI, the ERP of PVs was significantly increased to 245±38 msec as compared to that before the ablation (187±76 msec, p<0.001), which became much close to that of LA (234±43 ms, p>0.05). No influence of CPVI on LA ERP was found (p>0.05). The RRP and FRP of PVs were also significantly increased as compared to that before the ablation (230±47 msec vs 259±44 msec and 230±74 msec vs 298±47 msec, respectively, p<0.05), but there were no changes of LA RRP and FRP (256±49 msec vs 240±34 msec and 254±90 msec vs 276±47 msec, respectively, p>0.05). Conclusions: In patients with PAF, an ERP gradience from PVs to LA, and then to RA was observed, with the shortest in PVs and the longest in RA. The CPVI may have different impact on the electrophysiologic properties of PVs and LA. CPVI significantly decrease the arrhythmogenic of PVs and refractory heterogeneity between PVs and LA. These findings may help to explain the maintenance of sinus rhythm in a subgroup of patients with PAF by CPVI in spite of the PVs conduction already recovered.